PERANCANGAN BASIS DATA RELASIONAL PADA SISTEM REKAM MEDIS ELEKTRONIK PUSKESMAS XYZ - Naila Izzatul Kamilah; Tracy Gabriella Donda Sitorus; Aisyah Putriarta Lenggu; Zatin Niqotaini (Jurnal Riset Sistem Informasi, 2026)
Article 45 of the Regulation of the Minister of Health Number 24 of 2022 mandates all healthcare facilities in Indonesia to implement Electronic Medical Records (EMR). To comply with this regulation, XYZ Community Health Center (Puskesmas XYZ), whose data recording activities currently still rely on conventional or manual medical records, requires a digital transformation through the design of a structured and integrated database. This study aims to design the EMR database architecture at XYZ Community Health Center using the Entity Relationship Diagram (ERD) approach, which is then transformed into the Conceptual Data Model (CDM) and Physical Data Model (PDM) schemas. The methodology in this study was carried out systematically through a series of procedures, starting from problem identification, needs analysis, system design, design implementation, to drawing conclusions. This study successfully developed a database blueprint containing seven integrated main tables. The application of this data architecture is projected to contribute to accelerating the migration from manual systems to EMR, minimizing the risk of data redundancy, increasing service operational efficiency, ensuring the healthcare facility's compliance with government regulations.